The effect of emerging green market on green entrepreneurship and sustainable development in knowledge-based companies - Lotfi, Maryam; Yousefi, Akram; Jafari, Soheil (MDPI, 2018)
Environmental concerns, as well as consumers’ awareness of buying green or environmentally-friendly products, has a positive impact on the emergence of the green market. The emerging green market brings many opportunities in different fields. Today, the issue of green entrepreneurship and sustainable development aim at producing environmentally-friendly products. This is indeed welcomed in the emerging green market. The publicly available research studies that investigate how green entrepreneurship, sustainable development, and emerging green markets are interconnected with each other are limited. More specifically, the impact of the green market on green entrepreneurship and sustainable development has not yet been studied completely. Therefore, a comprehensive research model has been developed in this paper based on the literature. The developed model is then tested using IBM SPSS Statistics for Windows, Version 19. IBM Corp.: Armonk, NY, USA and Smart-PLS Version 2 based on the data collected via a survey from a sample of knowledge-based companies in the Science & Technology Park of Tehran University. The results of the research indicate a positive and significant effect of the emergence of the green market on green entrepreneurship and sustainable development in knowledge-based companies. Moreover, the impact of the green entrepreneurship structure on sustainable development has been studied and the result presents that green entrepreneurship has a positive and significant effect on sustainable development.
Keywords: green market; green entrepreneurship; sustainable development